Synergy to Strengthen the Quality of Islamic Education in Achieving Sustainable Development Goals (SDGs) - Chabibi, Chamim; Khudori Soleh, Achmad; Tharaba, M. Fahim; Asy'arie, Bima Fandi; Bunayar (Tafkir: Interdisciplinary Journal of Islamic Education, 2025)
This research aims to understand and analyze the leadership role of KH. Muhammad Tholhah Hasan is working to improve the quality of Islamic education to achieve sustainable development goals (SDGs). This research is field research with a multisite method and qualitative approach. There were 12 informants involved through interviews, with research locations at the Al-Ma'arif Foundation and the Sabilillah Foundation, Singosari District, Malang Regency, East Java. This research's findings include several roles: First, as the initiator, he sets long-term goals and manages change for educational sustainability. Second is the concept's role, where he carries out comprehensive planning and delegates responsibility to the next generation. Third, in reform, he leads decision-making through deliberation and considers risks to maintain the quality of education. Fourth, his organizational role involves "istikhoroh" and "riyadloh" before making big decisions. Fifth, as an actor, he carries out monitoring and cadre formation for leadership regeneration. Sixth, as a developer, he innovates the curriculum. He discusses with stakeholders how to adapt education to 21st-century skills and SDG goals, focusing on the quality of Islamic education and sustainability. This contribution can encourage the creation of an inclusive society, reduce inequality, and form a generation ready to face various global challenges in an era of rapid technological development.